Summer secrets - Freethy, Barbara (New York : New American Library, 2003)
Tyler Jamison, a reporter, goes to Castleton Island off the coast of Washington to try and pry the secret of what went on in the McKenna family during the summer eight years before. The three sisters and their father won an around the world challenge in their sailboat that summer, but seem haunted by the journey's aftermath. Tyler has a secret of his own, however, which could destroy his growing attraction for one of the sisters.
"An Onyx book."
Keywords: Fathers and daughters -- Fiction; Sisters -- Fiction; Alcoholism -- Fiction; Adoption -- Fiction; Reporters and reporting -- Fiction; Washington (State) -- Fiction; Love stories